(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article delves into the intricate interplay between clinical considerations and anatomical nuances in managing phlegmons of the eye area. From exploring the vascular and lymphatic systems to detailing surgical procedures and outcomes, it provides a comprehensive overview. The article underscores the significance of precise interventions and the delicate balance required in navigating anatomical structures during opening and drainage procedures.